Racial, Ethnic, and Age Disparities in Incidence and Survival of Intrahepatic Cholangiocarcinoma in the United States; 1995-2014 - Samuel O. Antwi; Omar Y. Mousa; Tushar Patel (Annals of Hepatology, 2018)
Introduction and aim. Despite reports of increased incidence of intrahepatic cholangiocarcinoma (iCCA) in the United States, the impact of age or influences of race and ethnicity are not clear. Disparities in iCCA outcomes across various population subgroups also are not readily recognized due to the rarity of this cancer. We examined ethnic, race, age, and gender variations in iCCA incidence and survival using data from the Surveillance, Epidemiology, and End Results Program (1995-2014).Material and methods. We assessed age-adjusted incidence rates, average annual percentage change in incidence, and hazard ratios (HRs) with 95% confidence intervals (CIs) for all-cause and iCCA-specific mortality.Results. Overall, 11,127 cases of iCCA were identified, with an age-adjusted incidence rate of 0.92 per 100,000. The incidence rate increased twofold, from 0.49 per 100,000 in 1995 to 1.49 per 100,000 in 2014, with an average annual rate of increase of 5.49%. The iCCA incidence rate was higher among persons age 45 years or older than those younger than 45 years (1.71 vs. 0.07 per 100,000), among males than females (0.97 vs. 0.88 per 100,000) and among Hispanics than non-Hispanics (1.18 vs. 0.89 per 100,000). Compared to non-Hispanics, Hispanics had poorer 5-year all-cause mortality (HR = 1.11, 95%CI: 1.05-1.19) and poorer iCCA-specific mortality (HR = 1.15, 95%CI: 1.07-1.24). Survival rates were poor also for individuals age 45 years or older, men, and Blacks and American Indians/Alaska Natives. Conclusion.ConclusionThe results demonstrate ethnic, race, age and gender disparities in iCCA incidence and survival, and confirm continued increase in iCCA incidence in the United States.